Laparoscopic-assisted transhiatal oesophagectomy: An experience from a tertiary care centre over 10 years - Sudheer Kanchodu; Hirdaya Hulas Nag (Journal of Minimal Access Surgery, 2023)
Background: Minimally invasive surgeries have become the standard of care in oesophageal surgeries, but the transhiatal approach is still not widely in practice. As in the open surgical approach, laparoscopic transhiatal oesophagectomy has been accepted by many centres worldwide. The laparoscopic-assisted transhiatal oesophagectomy (LATE) has become a time-tested surgery. Many centres across the world have shown its feasibility and superiority regarding the lymph node yield with less morbidity with the added advantage of laparoscopy. We are pleased to share our 10-year experience with LATE and the long-term follow-up. Materials and Methods: Retrospective analysis of prospectively maintained data from our tertiary care centre from January 2010 to January 2021. Forty-six out of 74 patients with carcinoma of the lower end of the oesophagus who underwent LATE were analysed retrospectively. Results: Our study group included 46 patients. Six patients who required conversion to open surgery and those who underwent different procedures were excluded. The mean operative time was 220 (140–360) min. The mean blood loss was 230 (100–500) ml. Four (8.69%) patients had neck leaks. Twelve (26.08%) patients had minor pulmonary complications and one (2.17%) patient had a major pulmonary complication in the form of acute respiratory distress syndrome. The median hospital stay was 10.5 (8–28) days and 90-day mortality was 2.17%. 45 (97.82%) patients had an R0 resection rate with a median lymph node yield of 21 (16–28). The median overall survival was 44 months, with a 3 years disease-free survival rate of 63.04% and a 5-year overall survival rate of 36.50%. Conclusion: LATE is feasible and safe for adenocarcinoma of lower third esophagus and GEJ (gastroesophageal junction). The laparoscopic magnified view of lower mediastinum provides a better vision for lymphadenectomy especially in the neoadjuvant group. It has all the added benefits of minimal invasive surgery with acceptable short and long term oncological results.